(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Identifying some factors associated with the incidence rate of infectious diseases in Son La province period 2016-2023. Method: Cross-sectional descriptive study combined with secondary data analysis. Results: The average monthly temperature was 22.5°C; the average monthly humidity was 79.0%; and the average monthly rainfall was recorded at 107.6 mm. The proportion of children fully vaccinated was 94.8%. From 2016 to 2023, the proportion of the population using clean water sources and the number of doctors per 10,000 population showed an increasing trend, while the proportion of the population using sanitary latrines and the poverty rate showed a decreasing trend. Humidity was moderately correlated with varicella (r = -0.383; p < 0.001) and dengue fever (r = 0.311; p = 0.004), while no significant or only weak correlations were found with other diseases. A strong negative correlation was observed between the proportion of the population using clean water sources and sanitary latrines and the incidence of hand, foot and mouth disease and diarrhea; and between the number of doctors per 10,000 population and the incidence of bacillary dysentery. The poverty rate was associated with influenza, diarrhea, mumps, amoebic dysentery, and hand, foot and mouth disease. Conclusion: A moderate correlation was found between humidity and both varicella and dengue fever, while no significant or only weak correlations were observed with other infectious diseases. Socioeconomic and healthcare factors were found to be associated with certain infectious diseases. No correlation was found between the rate of full vaccination among children and the incidence of infectious diseases included in the expanded program on immunization.